Anion exchange membrane material based on hydroxyl-containing quaternary ammonium salt side chain and preparation method of anion exchange membrane material
By copolymerizing inditin with dibenzofuran and dibenzo crown ether and grafting hydroxyl-containing quaternary ammonium salt, an anion exchange membrane with excellent stability and high ion conductivity was prepared, and anion exchange in the prior art was solved The problem of insufficient membrane stability achieves high-performance applications under high temperature and alkaline conditions.
Patent Information
- Application Number
- CN202411614293.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2024-12-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The stability of existing commercial anion exchange membranes under electrochemical conditions, including electrochemical stability and chemical/mechanical stability, is insufficient and it is difficult to meet the requirements of high ionic conductivity and mechanical strength.
The matrix is formed by copolymerization of isatin with dibenzofuran and dibenzo crown ether, and the hydroxyl-containing quaternary ammonium salt is grafted onto the polymer framework to prepare anion exchange with excellent basic stability and ionic conductivity. Membrane material. The method includes synthesis of copolymers, grafting side chains of hydroxyl-containing quaternary ammonium salts, preparing membranes and alkali exchange treatment, preparing membrane materials by solution casting method, and alkali exchange treatment in KOH solution.
The high ionic conductivity and mechanical stability of the film material can be used for a long time under alkaline conditions. The conductivity at 80°C can reach up to 102 mS/cm, and remains high after 600 hours of alkaline soaking. ionic conductivity.
Smart Images

Figure CN119143952A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of membrane materials, and more specifically to an anion exchange membrane material based on a hydroxyl quaternary ammonium salt side chain and a preparation method thereof. Background Art
[0002] Environmental issues related to fossil fuels have been increasing in recent years, and the development of pollution-free renewable energy is of vital importance. Hydrogen is well known for its clean nature and high energy efficiency. Hydrogen can be produced by many different methods, including natural gas reforming, electrolysis, direct solar water splitting, and so on. Among them, anion exchange membrane (AEM) water electrolysis hydrogen production technology has attracted widespread attention from researchers because of its ability to use cheap non-precious metal catalysts for efficient water electrolysis, and its advantages of high flexibility, high safety, high current density and low cost.
[0003] AEM needs to have high ionic conductivity, high alkaline stability and good mechanical properties. However, Yan Xupeng et al. pointed out in their article "The Current Development of Commercial Anion Exchange Membranes for Hydrogen Production by Water Electrolysis" that most commercial anion exchange membranes still have certain problems in terms of stability (including electrochemical stability and chemical / mechanical stability) under electrochemical conditions. Therefore, designing a new anion exchange membrane material with excellent stability, ionic conductivity and mechanical strength has become the key to solving the above problems. Summary of the invention
[0004] The object of the present invention is to overcome the deficiencies of the above-mentioned prior art, and to provide an anion exchange membrane material based on a quaternary ammonium salt side chain containing hydroxyl groups and a preparation method thereof, wherein the material is formed into a matrix by copolymerization of indigo carmine with at least one of dibenzofuran and dibenzocrown ether, and then the quaternary ammonium salt containing hydroxyl groups is grafted onto a polymer backbone to prepare an anion exchange membrane suitable for an alkaline water electrolyzer. The membrane material has excellent alkaline stability and ionic conductivity, and is suitable for long-term application.
[0005] In order to achieve the above object, the present invention adopts the following technical solution:
[0006] An anion exchange membrane material based on a hydroxyl quaternary ammonium salt side chain, the structural formula of the anion exchange membrane is as follows:
[0007] ;
[0008] In the general formula, the R structure is any of the following:
[0009] , , ;
[0010] m is a positive integer less than 100, and n is a positive integer.
[0011] A method for preparing an anion exchange membrane material based on a hydroxyl quaternary ammonium salt side chain, comprising the following steps:
[0012] (1) Synthetic copolymer: using indigo and dibenzo compounds as monomers, dichloromethane as solvent, and trifluoromethanesulfonic acid as catalyst, a superacid-catalyzed Friedel-Crafts reaction is used to synthesize polyindigo-dibenzofuran or polyindigo-dibenzocrown ether or polyindigo-dibenzofuran-dibenzocrown ether copolymer, wherein the dibenzo compound is at least one of dibenzofuran and dibenzocrown ether;
[0013] (2) Grafting quaternary ammonium salt side chains containing hydroxyl groups: dissolving the copolymer obtained in step (1) in dimethyl sulfoxide, adding epoxy quaternary ammonium salt to carry out a ring-opening reaction; after the reaction is completed, adding the reaction solution dropwise into anhydrous ether for precipitation, washing and drying the precipitate to obtain a copolymer grafted with quaternary ammonium salt side chains;
[0014] (3) preparing a membrane: dissolving the copolymer grafted with quaternary ammonium salt side chains prepared in step (2) in dimethyl sulfoxide, and preparing a membrane material by a solution casting method;
[0015] (4) Alkali exchange treatment: The membrane material obtained in step (3) is immersed in a KOH solution for alkaline exchange treatment to obtain an anion exchange membrane.
[0016] Furthermore, in step (1), the usage ratio of indigo carmine to dibenzoic acid compound, dichloromethane and trifluoromethanesulfonic acid is (1.00-4.50) g: (0.2-6) g: (8.5-21.5) ml: (5.50-22.00) ml.
[0017] Furthermore, the specific method of step (1) is: adding at least one of dibenzofuran and dibenzocrown ether and indigo carmine to dichloromethane, stirring evenly, adding trifluoromethanesulfonic acid under ice bath conditions, keeping in the ice bath for 30 to 60 minutes, and then reacting at room temperature for 30 to 120 minutes; after the reaction is completed, pouring the reaction solution into a NaHCO3 solution to precipitate a fibrous product, and washing and drying to obtain a yellow copolymer.
[0018] Furthermore, in step (2), the ratio of the copolymer to dimethyl sulfoxide and epoxy quaternary ammonium salt is (0.5-1) g: (15-30) mL: (0.25-0.68) g; and the epoxy quaternary ammonium salt is 2,3-epoxypropyltrimethylammonium chloride.
[0019] Furthermore, in step (2), the ring-opening reaction temperature is 115-130° C., and the reaction time is 12-24 h.
[0020] Furthermore, the specific method of step (3) is: dissolving the copolymer grafted with quaternary ammonium salt side chains in dimethyl sulfoxide, centrifugally filtering, pouring the filtrate into a culture dish, heating to evaporate the solvent; then adding deionized water to peel off the membrane material and wash away the residual solvent to obtain a yellow transparent membrane material.
[0021] Furthermore, the temperature used when heating to evaporate the solvent is 60°C.
[0022] Furthermore, in step (3), the ratio of the copolymer grafted with quaternary ammonium salt side chains to dimethyl sulfoxide is 0.5 g:15 mL.
[0023] Furthermore, in step (4), the concentration of the KOH solution is 1 mol / L, and the alkaline exchange treatment time is 24 to 72 hours.
[0024] The beneficial effects of the present invention are:
[0025] 1. Raw materials are readily available and low in cost: Anion exchange membranes based on at least one of dibenzofuran and dibenzocrown ether and indigo carmine have a wide range of raw material sources and a simple preparation process, and are suitable for large-scale industrial production.
[0026] 2. Excellent ionic conductivity: Through the copolymerization of at least one of dibenzofuran and dibenzocrown ether with indigo carmine and the grafting modification of epoxy quaternary ammonium salt, the membrane can maintain a high ionic conductivity, and the conductivity at 80°C can reach up to 102 mS / cm.
[0027] 3. The membrane material has good stability: the membrane material modified by copolymerization of at least one of dibenzofuran and dibenzocrown ether with indigo carmine and grafting of epoxy quaternary ammonium salt exhibits good mechanical stability, dimensional stability and alkali resistance, and can still maintain a high ionic conductivity after being immersed in alkaline conditions for 600 hours. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 Graph showing the ion exchange capacity of the membranes prepared in Examples 1 to 6;
[0029] Figure 2 The ionic conductivity curves of the membranes prepared in Examples 1 to 6 at different temperatures;
[0030] Figure 3 The hydrogen nuclear magnetic resonance spectra of the films prepared in Examples 1 to 6;
[0031] Figure 4 The mechanical properties test results of the films prepared in Examples 1 to 6 are shown in FIG.
[0032] Figure 5The ionic conductivity curves of the membranes prepared in Example 1, Example 4 and Example 6 after being immersed in alkaline conditions for different time periods are shown. DETAILED DESCRIPTION
[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] The preparation method of the anion exchange membrane material based on the hydroxyl quaternary ammonium salt side chain of the present invention is:
[0035] (1) Synthesis of copolymers: Using isatin and a dibenzo compound (at least one of dibenzofuran and dibenzocrown ether, preferably dibenzo-18-crown-6) as monomers, dichloromethane as solvent, and trifluoromethanesulfonic acid (TFSA) as catalyst, a superacid-catalyzed Friedel-Crafts reaction is used to synthesize polyisatin-dibenzofuran or polyisatin-dibenzocrown ether or polyisatin-dibenzofuran-dibenzocrown ether copolymers. The amount ratio of isatin to dibenzo compound, dichloromethane, and trifluoromethanesulfonic acid is preferably (1.00-4.50) g: (0.2-6) g: (8.5-21.5) ml: (5.50-22.00) ml.
[0036] The specific method is as follows: at least one of benzofuran and dibenzocrown ether and indigo carmine are added to dichloromethane, and after stirring evenly, trifluoromethanesulfonic acid is added in an ice bath (-5~0°C), and the reaction is maintained for 30~60 minutes under the ice bath condition, and then reacted at room temperature for 30~120 minutes; after the reaction is completed, the reaction solution is poured into a 1mol / L NaHCO3 solution, a fibrous product is precipitated, and after multiple washings, it is dried to obtain a yellow polymer.
[0037] (2) Grafting hydroxyl-containing quaternary ammonium salt side chains: dissolve the copolymer obtained in step (1) in dimethyl sulfoxide, add epoxy quaternary ammonium salt (preferably 2,3-epoxypropyltrimethylammonium chloride), and carry out ring-opening reaction at 115-130°C for 12-24 hours. The ratio of polymer to dimethyl sulfoxide and epoxy quaternary ammonium salt is preferably (0.5-1) g: (15-30) mL: (0.25-0.68) g. After the reaction is completed, add the reaction solution dropwise into anhydrous ether for precipitation. After the precipitate is dried in vacuum, the copolymer grafted with quaternary ammonium salt side chains is obtained.
[0038] (3) Preparing membrane material by solution casting method: dissolving the copolymer grafted with quaternary ammonium salt side chains prepared in step (2) in dimethyl sulfoxide (the ratio of the copolymer grafted with quaternary ammonium salt side chains to dimethyl sulfoxide is preferably 0.5 g:15 mL), centrifugally filtering, pouring the filtrate into a culture dish, and heating at 60°C to evaporate the solvent; then adding deionized water to peel off the membrane material and wash away the residual solvent to obtain a yellow transparent anion exchange membrane.
[0039] (4) Alkali exchange treatment: The membrane material obtained in step (3) is immersed in a 1 mol / L KOH solution for alkaline exchange treatment for 24 to 72 hours to obtain an anion exchange membrane.
[0040] The structural formula of the anion exchange membrane prepared by the present invention is as follows:
[0041] ;
[0042] In the general formula, the R structure is any of the following:
[0043] , , ;
[0044] m is a positive integer less than 100, and n is a positive integer.
[0045] The preferred embodiments are as follows:
[0046] Example 1
[0047] In 15 mL of dichloromethane, add 2.62 g of indigo carmine and 2.00 g of dibenzofuran, stir evenly, add 9.5 mL of trifluoromethanesulfonic acid in an ice bath (-5°C), and keep the reaction for 30 minutes under the ice bath, and then continue the reaction at room temperature for 4 hours. After the reaction is completed, pour the product into a 1M NaHCO3 solution to precipitate a yellow fibrous product, crush the product and stir it in a 1M NaHCO3 solution for 12 h, then wash the product with deionized water and dry it to obtain a polyindigo carmine-dibenzofuran polymer. Subsequently, 0.5 g of the polymer was dissolved in 15 mL of dimethyl sulfoxide (DMSO), and 0.3825 g of 2,3-epoxypropyltrimethylammonium chloride was added. The reaction was carried out at 120 ° C for 24 hours. After the reaction was completed, the reaction solution was added dropwise to anhydrous ether for precipitation. After standing overnight, the precipitated solid was cut into pieces and further stirred and washed twice with deionized water. The precipitate was vacuum dried to obtain a deep red polymer with grafted quaternary ammonium salt side chains. The prepared polymer with grafted quaternary ammonium salt side chains was dissolved in dimethyl sulfoxide (the ratio of the polymer with grafted quaternary ammonium salt side chains to dimethyl sulfoxide was 0.5 g: 15 ml), centrifuged and filtered, and the filtrate was poured into a culture dish and heated at 60 ° C to evaporate the solvent; then deionized water was added to peel off the membrane material and wash away the residual solvent to obtain a yellow transparent membrane material. The membrane material was soaked in 1 mol / L KOH for 48 hours and then washed with deionized water to obtain a yellow transparent anion exchange membrane containing hydroxyl quaternary ammonium salt side chains, and its Cl - Conductivity (80°C) 63 mS / cm -1 .
[0048] Example 2
[0049] In 15 mL of dichloromethane, add 2.62 g of indigo carmine and 2.00 g of dibenzofuran, stir evenly, add 9.5 mL of trifluoromethanesulfonic acid in an ice bath (-5°C), and keep the reaction for 30 minutes under the ice bath, and then continue the reaction at room temperature for 4 hours. After the reaction is completed, pour the product into a 1M NaHCO3 solution to precipitate a yellow fibrous product, crush the product and stir it in a 1M NaHCO3 solution for 12 h, then wash the product with deionized water and dry it to obtain a polyindigo carmine-dibenzofuran polymer. Subsequently, 0.5 g of the polymer was dissolved in 15 mL of dimethyl sulfoxide (DMSO), and 0.2043 g of 2,3-epoxypropyltrimethylammonium chloride was added. The reaction was carried out at 120 ° C for 24 hours. After the reaction was completed, the reaction solution was added dropwise to anhydrous ether for precipitation. After standing overnight, the precipitated solid was cut into pieces and further stirred and washed twice with deionized water. The precipitate was vacuum dried to obtain a deep red polymer with grafted quaternary ammonium salt side chains. The prepared polymer with grafted quaternary ammonium salt side chains was dissolved in dimethyl sulfoxide (the ratio of the polymer with grafted quaternary ammonium salt side chains to dimethyl sulfoxide was 0.5 g: 15 ml), centrifuged and filtered, and the filtrate was poured into a culture dish and heated at 60 ° C to evaporate the solvent; then deionized water was added to strip the membrane material and wash away the residual solvent to obtain a yellow transparent membrane material. The membrane material was soaked in 1 mol / L KOH for 48 hours and then washed with deionized water to obtain a yellow transparent anion exchange membrane containing hydroxyl quaternary ammonium salt side chains, and its Cl - Conductivity (80°C) 31 mS / cm -1 .
[0050] Example 3
[0051] 1.12 g of indigo, 0.23 g of dibenzofuran and 2 g of dibenzo-18-crown-6 were added to 8.5 mL of dichloromethane, stirred evenly, and then 6 mL of trifluoromethanesulfonic acid was added in an ice bath (-5°C), and the reaction was kept for 1 hour under the ice bath, and then the reaction was continued at room temperature for 120 minutes. After the reaction was completed, the product was poured into a 1M NaHCO3 solution, and a yellow fibrous product was precipitated. The product was crushed and stirred in a 1M NaHCO3 solution for 12 h, and then the product was washed with deionized water and dried to obtain a polyindigo-dibenzofuran-dibenzocrown copolymer. Subsequently, 0.5 g of the copolymer was dissolved in 15 mL of dimethyl sulfoxide (DMSO), and 0.2522 g of 2,3-epoxypropyltrimethylammonium chloride was added. The reaction was carried out at 120 ° C for 24 hours. After the reaction was completed, the reaction solution was added dropwise to anhydrous ether for precipitation. After standing overnight, the precipitated solid was cut into pieces and further stirred and washed twice with deionized water. The precipitate was vacuum dried to obtain a deep red copolymer with grafted quaternary ammonium salt side chains. The prepared copolymer with grafted quaternary ammonium salt side chains was dissolved in dimethyl sulfoxide (the ratio of the copolymer with grafted quaternary ammonium salt side chains to dimethyl sulfoxide was 0.5 g: 15 ml), centrifuged and filtered, and the filtrate was poured into a culture dish and heated at 60 ° C to evaporate the solvent; then deionized water was added to strip the membrane material and wash away the residual solvent to obtain a yellow transparent membrane material. The membrane material was soaked in 1 mol / L KOH for 48 hours and then washed with deionized water to obtain a yellow transparent anion exchange membrane containing hydroxyl quaternary ammonium salt side chains, and its Cl - Conductivity (80°C) 88 mS / cm -1 .
[0052] Example 4
[0053] 1.79 g of indigo, 0.93 g of dibenzofuran and 2.00 g of dibenzo-18-crown-6 were added to 11 mL of dichloromethane, stirred evenly, and then 9 mL of trifluoromethanesulfonic acid was added in an ice bath (-5°C), and the reaction was kept for 1 hour under the ice bath, and then the reaction was continued at room temperature for 90 minutes. After the reaction was completed, the product was poured into a 1M NaHCO3 solution, and a yellow fibrous product was precipitated. The product was crushed and stirred in a 1M NaHCO3 solution for 12 h, and then the product was washed with deionized water and dried to obtain a polyindigo-dibenzofuran-dibenzocrown copolymer. Subsequently, 0.5 g of the copolymer was dissolved in 15 mL of dimethyl sulfoxide (DMSO), and 0.2892 g of 2,3-epoxypropyltrimethylammonium chloride was added. The reaction was carried out at 120 ° C for 24 hours. After the reaction was completed, the reaction solution was added dropwise to anhydrous ether for precipitation. After standing overnight, the precipitated solid was cut into pieces and further stirred and washed twice with deionized water. The precipitate was vacuum dried to obtain a deep red copolymer with grafted quaternary ammonium salt side chains. The prepared copolymer with grafted quaternary ammonium salt side chains was dissolved in dimethyl sulfoxide (the ratio of the copolymer with grafted quaternary ammonium salt side chains to dimethyl sulfoxide was 0.5 g: 15 ml), centrifuged and filtered, and the filtrate was poured into a culture dish and heated at 60 ° C to evaporate the solvent; then deionized water was added to strip the membrane material and wash away the residual solvent to obtain a yellow transparent membrane material. The membrane material was soaked in 1 mol / L KOH for 48 hours and then washed with deionized water to obtain a yellow transparent anion exchange membrane containing hydroxyl quaternary ammonium salt side chains, and its Cl - Conductivity (80°C) 102 mS / cm -1 .
[0054] Example 5
[0055] 4.49 g of indigo, 3.71 g of dibenzofuran and 2 g of dibenzo-18-crown-6 were added to 21.5 mL of dichloromethane, stirred evenly, and then 22 mL of trifluoromethanesulfonic acid was added in an ice bath (-5°C), and the reaction was kept for 1 hour under the ice bath, and then continued to react at room temperature for 60 minutes. After the reaction was completed, the product was poured into a 1M NaHCO3 solution, and a yellow fibrous product was precipitated. The product was crushed and stirred in a 1M NaHCO3 solution for 12 h, and then the product was washed with deionized water and dried to obtain a polyindigo-dibenzofuran-dibenzocrown copolymer. Subsequently, 0.5 g of the copolymer was dissolved in 15 mL of dimethyl sulfoxide (DMSO), and 0.3390 g of 2,3-epoxypropyltrimethylammonium chloride was added. The reaction was carried out at 120 ° C for 24 hours. After the reaction was completed, the reaction solution was added dropwise to anhydrous ether for precipitation. After standing overnight, the precipitated solid was cut into pieces and further stirred and washed twice with deionized water. The precipitate was vacuum dried to obtain a deep red copolymer with grafted quaternary ammonium salt side chains. The prepared copolymer with grafted quaternary ammonium salt side chains was dissolved in dimethyl sulfoxide (the ratio of the copolymer with grafted quaternary ammonium salt side chains to dimethyl sulfoxide was 0.5 g: 15 ml), centrifuged and filtered, and the filtrate was poured into a culture dish and heated at 60 ° C to evaporate the solvent; then deionized water was added to peel off the membrane material and wash away the residual solvent to obtain a yellow transparent membrane material. The membrane material was soaked in 1 mol / L KOH for 48 hours and then washed with deionized water to obtain a yellow transparent anion exchange membrane containing hydroxyl quaternary ammonium salt side chains, and its Cl - Conductivity (80°C) 48 mS / cm -1 .
[0056] Example 6
[0057] 1.0 g of indigo and 2.0 g of dibenzo-18-crown-6 were added to 12 mL of dichloromethane, stirred evenly, and then 5.5 mL of trifluoromethanesulfonic acid was added in an ice bath (-5°C), and the reaction was kept for 1 hour under the ice bath, and then continued to react at room temperature for 30 minutes. After the reaction was completed, the product was poured into a 1M NaHCO3 solution, and a yellow fibrous product was precipitated. The product was crushed and stirred in a 1M NaHCO3 solution for 12 h, and then the product was washed with deionized water and dried to obtain a polyindigo-dibenzocrown polymer. Subsequently, 0.5 g of the polymer was dissolved in 15 mL of dimethyl sulfoxide (DMSO), and 0.2323 g of 2,3-epoxypropyltrimethylammonium chloride was added. The reaction was carried out at 120 ° C for 24 hours. After the reaction was completed, the reaction solution was added dropwise to anhydrous ether for precipitation. After standing overnight, the precipitated solid was cut into pieces and further stirred and washed twice with deionized water. The precipitate was vacuum dried to obtain a deep red polymer with grafted quaternary ammonium salt side chains. The prepared polymer with grafted quaternary ammonium salt side chains was dissolved in dimethyl sulfoxide (the ratio of the polymer with grafted quaternary ammonium salt side chains to dimethyl sulfoxide was 0.5 g: 5 ml), centrifuged and filtered, and the filtrate was poured into a culture dish and heated at 60 ° C to evaporate the solvent; then deionized water was added to strip the membrane material and wash away the residual solvent to obtain a yellow transparent membrane material. The membrane material was soaked in 1 mol / L KOH for 48 hours and then washed with deionized water to obtain a yellow transparent anion exchange membrane containing hydroxyl quaternary ammonium salt side chains, and its Cl - Conductivity (80°C) 59 mS / cm -1 .
[0058] The anion exchange membranes containing hydroxyl quaternary ammonium salt side chains prepared in Examples 1 to 6 were subjected to structural characterization and performance testing. The ion exchange capacity of each membrane material is as follows: Figure 1 As shown in Figure 2, the ionic conductivity at different temperatures is Figure 2 As shown, the H NMR spectrum is Figure 3 As shown, the mechanical properties are Figure 4 As shown; the ionic conductivity of the membranes prepared in Examples 1, 4, and 6 after being immersed in alkaline conditions for different periods of time is as shown Figure 5 shown.
[0059] The above is only a preferred embodiment of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, some improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.
Claims
1. An anion exchange membrane material based on a quaternary ammonium salt side chain containing hydroxyl groups, characterized in that: The structural formula of the anion exchange membrane is as follows: ; In the general formula, the R structure is any of the following: 、 、 ; m is a positive integer less than 100, and n is a positive integer.
2. A method for preparing an anion exchange membrane material based on a hydroxyl quaternary ammonium salt side chain according to claim 1, characterized in that: Here are the steps: (1) Synthetic copolymer: using indigo and dibenzo compounds as monomers, dichloromethane as solvent, and trifluoromethanesulfonic acid as catalyst, a superacid-catalyzed Friedel-Crafts reaction is used to synthesize polyindigo-dibenzofuran or polyindigo dibenzocrown ether or polyindigo-dibenzofuran-dibenzocrown ether copolymer, wherein the dibenzo compound is at least one of dibenzofuran and dibenzocrown ether; (2) Grafting quaternary ammonium salt side chains containing hydroxyl groups: dissolving the copolymer obtained in step (1) in dimethyl sulfoxide, adding epoxy quaternary ammonium salt to carry out a ring-opening reaction; after the reaction is completed, adding the reaction solution dropwise into anhydrous ether for precipitation, washing and drying the precipitate to obtain a copolymer grafted with quaternary ammonium salt side chains; (3) preparing a membrane: dissolving the copolymer grafted with quaternary ammonium salt side chains prepared in step (2) in dimethyl sulfoxide, and preparing a membrane material by a solution casting method; (4) Alkali exchange treatment: The membrane material obtained in step (3) is immersed in a KOH solution for alkaline exchange treatment to obtain an anion exchange membrane.
3. A method for preparing an anion exchange membrane material based on a hydroxyl quaternary ammonium salt side chain according to claim 2, characterized in that: In step (1), the usage ratio of indigo carmine to dibenzoic acid compound, dichloromethane and trifluoromethanesulfonic acid is (1.00-4.50) g: (0.2-6) g: (8.5-21.5) ml: (5.50-22.00) ml.
4. A method for preparing an anion exchange membrane material based on a hydroxyl quaternary ammonium salt side chain according to claim 2, characterized in that: The specific method of step (1) is as follows: at least one of dibenzofuran and dibenzocrown ether and indigo carmine are added to dichloromethane, and after stirring evenly, trifluoromethanesulfonic acid is added under ice bath conditions, and the mixture is kept in the ice bath for 30 to 60 minutes and then reacted at room temperature for 30 to 120 minutes; after the reaction is completed, the reaction solution is poured into a NaHCO3 solution to precipitate a fibrous product, which is washed and dried to obtain a yellow copolymer.
5. A method for preparing an anion exchange membrane material based on a hydroxyl quaternary ammonium salt side chain according to claim 2, characterized in that: In step (2), the ratio of the copolymer to dimethyl sulfoxide and epoxy quaternary ammonium salt is (0.5-1) g: (15-30) mL: (0.25-0.68) g; the epoxy quaternary ammonium salt is 2,3-epoxypropyltrimethylammonium chloride.
6. A method for preparing an anion exchange membrane material based on a hydroxyl quaternary ammonium salt side chain according to claim 2, characterized in that: In step (2), the ring-opening reaction temperature is 115-130°C, and the reaction time is 12-24h.
7. A method for preparing an anion exchange membrane material based on a hydroxyl quaternary ammonium salt side chain according to claim 2, characterized in that: The specific method of step (3) is as follows: dissolving the copolymer grafted with quaternary ammonium salt side chains in dimethyl sulfoxide, centrifugally filtering, pouring the filtrate into a culture dish, heating to evaporate the solvent; then adding deionized water to peel off the membrane material and wash away the residual solvent to obtain a yellow transparent membrane material.
8. A method for preparing an anion exchange membrane material based on a hydroxyl quaternary ammonium salt side chain according to claim 7, characterized in that: The temperature used when heating to evaporate the solvent was 60°C.
9. A method for preparing an anion exchange membrane material based on a hydroxyl quaternary ammonium salt side chain according to claim 2, characterized in that: In step (3), the ratio of the copolymer grafted with quaternary ammonium salt side chains to dimethyl sulfoxide is 0.5 g:15 mL.
10. The method for preparing an anion exchange membrane material based on a hydroxyl quaternary ammonium salt side chain according to claim 2, characterized in that: In step (4), the concentration of KOH solution is 1 mol / L, and the alkali exchange treatment time is 24 to 72 hours.
Citation Information
Patent Citations
Long side chain type polyarene isatin alkaline membrane for fuel cell and preparation method of long side chain type polyarene isatin alkaline membrane
CN112898539A
Polydibenzofuran indole anion exchange membrane and preparation method thereof
CN116487665A
Preparation process of electrolyte membrane material containing conjugated structure
CN118852593A
